STUDENTS’ INTEREST TOWARD THE USE OF MIND MAPPING IN WRITING PROCEDURE TEXT AT THE TENTH GRADE OF SMAN 22 MAKASSAR - Sunar Sadani; Sulviana S; Jusmaniar N (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2025)
Mind mapping is known as a visualization technique that can help students organize ideas systematically before writing, so that the writing process becomes more structured and easier to understand. This study aimed to investigate the students' interest in using mind mapping as a tool in writing procedural texts, especially among 10th grade students of SMAN 22 Makassar. This study was a quantitative approach with a survey. It was used as the main instrument to collect data from respondents. A total of 36 questions were arranged in the form of a questionnaire and distributed to 32 students from tenth grade. These questions were designed to assess the extent of interest, understanding, and effectiveness of using mind mapping in supporting procedural text writing activities. Most students showed a positive interest in using mind mapping in writing learning. They considered this technique very helpful in compiling and developing ideas related to procedural steps more clearly and systematically. In addition, mind mapping was also considered to be able to improve students' creativity and critical thinking skills when writing. However, there were some students who experienced obstacles, especially in understanding how to compile an effective mind map. This study showed the importance of the teacher's role in providing guidance, examples, and repeated practice so that students can apply this technique optimally. With the right support, mind mapping has great potential as an effective tool in teaching writing, especially for procedural texts at the high school level.